NILAI PERUSAHAAN DALAM PERBEDAAN PENGARUH PENERAPAN GCG TERHADAP KINERJA KEUANGAN BUMN MASA KEPEMIMPINAN JOKOWI (2015-2022) - syahrudin, muhammad; fitriana, Fitriana; Suryani, Irma (Department of Accounting-Faculty of Economic and Business (FEB), 2024)
The Jokowi administration has restructured the number of SOEs since 2016 to 41 SOEs in 2022. However, the reduction in the number of SOEs each year does not reduce the practice of fraud or fraud within SOEs in Indonesia. State-Owned Enterprises (BUMN) are alleged to be wetlands and vulnerable to acts of corruption due to the large number of very lucrative big projects. Fraud harms state-owned enterprises with a percentage of 31.8% then private companies 15.1%, the first rank is occupied by government agencies with a percentage of 48.5% based on ACFE data.To find out the differences in the effect of implementing GCG on firm value as an intervening variable on company performance in BUMN companies in the first and second periods of Jokowi's leadership (2015-2022) is the aim of this study.State-Owned Enterprises in the infrastructure sector listed on the IDX during 2015 to 2022 totaling 8 BUMNs were used as the population in this study. Path analysis and the Wilcoxon test were used in this research method using the help of Eviews 9 SoftwareThe results showed that Institutional Share Ownership and the Independent Board of Commissioners had an effect on Firm Value and Managerial Share Ownership and Audit Committee had no effect on Firm Value then there was a significant difference in construction cluster SOEs between leadership period I (2015-2018) and leadership period II (2019- 2022) President Joko Widodo.